TENDENCIES OF DEVELOPMENT OF PRODUCTION IN INDUSTRY - Tukhtaeva Nazokat Rustamovna (Ecominds Press, 2025)
Industrial production has always been the main foundation of economic development. In recent years, the development trends of industrial production have shown significant changes. Globally, the industrial sector is developing by adopting the principles of technological innovation, digital transformation and sustainable development. This article analyzes the main development trends of industrial production and considers their impact on economic, environmental and social aspects. Industrial trends play an important role in driving economic growth, creating new jobs, technological innovations and global economic connections around the world.
Keywords: Artificial intelligence, robotics, digital transformation, smart production, green energy, globalization.